2007
DOI: 10.1590/s0100-879x2006005000125
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and cytotoxicity of cisplatin-containing liposomes

Abstract: We encapsulated cisplatin into stealth pH-sensitive liposomes and studied their stability, cytotoxicity and accumulation in a human small-cell lung carcinoma cell line (GLC4) and its resistant subline (GLC4/CDDP). Since reduced cellular drug accumulation has been shown to be the main mechanism responsible for resistance in the GLC4/CDDP subline, we evaluated the ability of this new delivery system to improve cellular uptake. The liposomes were composed of dioleoylphosphatidylethanolamine (DOPE), cholesteryl he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 27 publications
0
27
1
Order By: Relevance
“…10 In our study, IC50 of CDDP against A549 cells was 2.35 times that of NLE-CDDP (2.63 µg/mL vs 1.12 µg/mL), which was higher than the 1.34 times reported by Carvalho et al 11 In addition, in vivo tests also demonstrated much stronger tumor inhibitions in NLE-CDDP than those in CDDP, indicating that the cytotoxicity of our NLE-CDDP was more significant than the cytotoxicity of CDDP. The strong toxicity of NLE-CDDP may be attributed to its small size (100 nm), which is smaller than that reported in the literature (174 nm).…”
Section: Discussioncontrasting
confidence: 64%
“…10 In our study, IC50 of CDDP against A549 cells was 2.35 times that of NLE-CDDP (2.63 µg/mL vs 1.12 µg/mL), which was higher than the 1.34 times reported by Carvalho et al 11 In addition, in vivo tests also demonstrated much stronger tumor inhibitions in NLE-CDDP than those in CDDP, indicating that the cytotoxicity of our NLE-CDDP was more significant than the cytotoxicity of CDDP. The strong toxicity of NLE-CDDP may be attributed to its small size (100 nm), which is smaller than that reported in the literature (174 nm).…”
Section: Discussioncontrasting
confidence: 64%
“…PTX is widely used as a first-line treatment for patients with breast cancer; however, this drug is highly hydrophobic and the use of liposomes as carriers for PTX has been frequently explored [10,12,14]. Our research group has developed long-circulating and pH-sensitive liposomes containing other antitumor drugs, such as cisplatin and ursolic acid, which have showed a marked enhancement of the in vitro and in vivo anticancer activity as well as reduced toxicity [26][27][28]. These systems are generally stable at physiological pH but can undergo destabilization and acquire fusogenic properties under acid conditions at the endosomal stage, thus leading to the drug release into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal cisplatin was shown to be more effective and less toxic to non-cancer cells in liposomal forms in comparison with solutions. Also, long-circulating liposomes are considered to overcome drug resistance [40][41][42][43] and in general present a promising delivery system for cisplatin-based cancer treatment.…”
Section: +mentioning
confidence: 99%